Structure-based design of a single-chain triple-disulfide-stabilized fusion-glycoprotein trimer that elicits high-titer neutralizing responses against human metapneumovirus. - Li Ou; Steven J Chen; I-Ting Teng; Lijuan Yang; Baoshan Zhang; Tongqing Zhou; Andrea Biju; Cheng Cheng; Wing-Pui Kong; Nicholas C Morano; Erik-Stephane D Stancofski; John-Paul Todd; et al. (PLoS Pathogens, 2023)
The Pneumoviridae family of viruses includes human metapneumovirus (HMPV) and respiratory syncytial virus (RSV). The closely related Paramyxoviridae family includes parainfluenza viruses (PIVs). These three viral pathogens cause acute respiratory tract infections with substantial disease burden in the young, the elderly, and the immune-compromised. While promising subunit vaccines are being developed with prefusion-stabilized forms of the fusion glycoproteins (Fs) of RSV and PIVs, for which neutralizing titers elicited by the prefusion (pre-F) conformation of F are much higher than for the postfusion (post-F) conformation, with HMPV, pre-F and post-F immunogens described thus far elicit similar neutralizing responses, and it has been unclear which conformation, pre-F or post-F, would be the most effective HMPV F-vaccine immunogen. Here, we investigate the impact of further stabilizing HMPV F in the pre-F state. We replaced the furin-cleavage site with a flexible linker, creating a single chain F that yielded increased amounts of pre-F stabilized trimers, enabling the generation and assessment of F trimers stabilized by multiple disulfide bonds. Introduced prolines could increase both expression yields and antigenic recognition by the pre-F specific antibody, MPE8. The cryo-EM structure of a triple disulfide-stabilized pre-F trimer with the variable region of antibody MPE8 at 3.25-Å resolution confirmed the formation of designed disulfides and provided structural details on the MPE8 interface. Immunogenicity assessments in naïve mice showed the triple disulfide-stabilized pre-F trimer could elicit high titer neutralization, >10-fold higher than elicited by post-F. Immunogenicity assessments in pre-exposed rhesus macaques showed the triple disulfide-stabilized pre-F could recall high neutralizing titers after a single immunization, with little discrimination in the recall response between pre-F and post-F immunogens. However, the triple disulfide-stabilized pre-F adsorbed HMPV-directed responses from commercially available pooled human immunoglobulin more fully than post-F. Collectively, these results suggest single-chain triple disulfide-stabilized pre-F trimers to be promising HMPV-vaccine antigens.